The witch's boy - Barnhill, Kelly Regan (Algonquin Young Readers, 2014)
When a Bandit King comes to take the magic that Ned's mother, a witch, is meant to protect, the stuttering, weak boy villagers think should have drowned rather than his twin summons the strength to protect his family and community, while in the woods, the bandit's daughter puzzles over a mystery that ties her to Ned.